Atlas of Pediatric Cardiac Surgery - Mavroudis, Constantine; Backer, Carl Lewis (Springer London : Imprint: Springer, 2015)
This atlas addresses the numerous changes and advances that have occurred in the field of congenital heart surgery over the last few years, resulting in improved techniques and new operations. The sheer number of new procedures and the required attendant technical skills to successfully complete an operation have become a challenge to master, especially for residents who are pursuing a career in congenital heart surgery The atlas is organized generally by anomaly and the procedure pertaining thereto. Two general sections involve cannulation techniques and palliative procedures. A special section depicts difficult problems in the form of clinical vignettes that may arise during cardiopulmonary bypass, such as decreased venous return, undiagnosed patent ductus arteriosus, and technical errors leading to hemodynamic complications. The Atlas of Pediatric Cardiac Surgery is an educational and beautifully illustrated atlas of congenital heart surgery that explains and illustrates procedures that cover the breadth of congenital heart surgery, appealing to trainee and practicing pediatric cardiac surgeons, cardiologists and interventionalists, pediatricians, and pediatric critical care physicians alike.